UJI KEBOCORAN APRON MENGGUNAKAN PESAWAT SINAR-X FLUOROSKOPI DI RSUD M. NATSIR SOLOK TAHUN 2021: . - Nansih, Livia Ade (JURNAL TERAS KESEHATAN, 2022)
The Apron is a lead apron to protect the body from radiation hazards, to reduce exposure to fluoroscopy radiation, and made of lead as a shield. Based on observations, the number of aprons was seven, purchased in 2011 and 2012. The apron was placed on a small table, and the wrong apron was found. Seven of the aprons, one of which was on the first apron, were suspected to have been damaged due to the wrong way of storing the apron and the researcher noticed kinks in the suspected apron. This type of research is quantitative, in the Radiology Unit of RSUD. Mohammad Natsir Solok from January 2021. Population 7 apron, sample 7 apron, data processing by measuring using tools available in fluoroscopy, data analysis compared with Lambert and McKeon (2001) theory. The results showed that the leak in the upper one apron was 51.54 mm2, the lower part 38.21 mm2 in the lower two apron 51.43 mm2, the third apron in the middle right front area was 21.12 mm2, in the lower right front area 1.664,87 mm2, at the rear center area 1,435.57 mm2, the top five rear area apron 6.97 mm2, at the rear center area 26.98 mm2